Human Embryos, Induced Pluripotent Stem Cells, and Organoids: Models to Assess the Effects of Environmental Plastic Pollution - Miloradovic, Dragana; Pavlovic, Dragica; Jankovic, Marina Gazdic; Nikolic, Sandra; Papic, Milos; Milivojevic, Nevena; Stojkovic, Miodrag; Ljujic, Biljana (Frontiers in Cell and Developmental Biology, 2021)
For a long time, animal models were used to mimic human biology and diseases. However, animal models are not an ideal solution due to numerous interspecies differences between humans and animals. New technologies, such as human-induced pluripotent stem cells and 3D cultures such as organoids, represent promising solutions for replacing, refining, and reducing animal models. The capacity of organoids to differentiate, self-organize, and form specific, complex, biologically suitable structures makes them excellent in vitro models of development and disease pathogenesis, as well as drug screening platforms. Despite significant potential health advantages, further studies and considerable nuances are necessary before their clinical use. This chapter summarizes the definition of embryoids, gastruloids, and organoids, and clarifies their appliance as models for early development, diseases, environmental pollution, drug screening, and bioinformatics.